AN ERROR ANALYSIS OF SCIENTIFIC PAPERS WRITTEN BY PUBLIC HEALTH STUDY PROGRAM STUDENTS OF STIK BINA HUSADA PALEMBANG - Agus Wahyudi (Didascein : Journal of English Education, 2022)
One of the student's obligations as a graduation requirement is to write a thesis. Scientific writing is written work that is systematically arranged according to certain rules according to the results of scientific thinking. There are several types of scientific work reports, namely: research reports, scientific works, dissertations, and proposals.  Abstract is an important part of a scientific work located on the first page of a scientific paper.Abstract is a brief description of a scientific work, background, questions, methods used, results obtained, conclusions, and recommendations. This paper discussed the results of the analysis of the errors in English abstract of postgraduate students STIK Bina Husada Palembang majoring Public Health Study Program in Scientific Writing Course. The design of this type of research was observational with a descriptive approach. The aim was to collect data through observation of scientific documents which aims to explain the feasibility of writing the English abstracts. 100% abstracts were appropriate in giving background detail, 70% were appropriate in describing the research activity and stating the conclusion, while reporting result only 60% and 40% describing the methods were appropriate. Google Translate sometimes cannot convert the word meanings appropriately, such as Posyandu, Gasurkes, and Perwali. The students must recheck their work and not rely solely on the translation application.Keywords:error, analysis, scientific papers